The Impact of Internal Integration on Logistics Speed and Reliability: The Mediating Role of Customer Integration - Ahmet Çetindaş; Mazlum Çelik (Journal of Transportation and Logistics)
The objective of this research is to investigate the impact of internal integration on speed and reliability in logistics and the mediating role of customer integration. Toward this aim, the study collected data from 161 manufacturing companies operating in Gaziantep by applying the scales through questionnaires. The analysis essential to the research have been conducted using the programs SPSS and AMOS. The results prove internal integration to positively impact customer integration, and customer integration to positively impact logistics speed and reliability. Internal integration’s impact on logistic speed and reliability could not be proven with the structural equation model. However, the process macro results revealed internal integration to positively impact speed and reliability in logistics. Furthermore, the results from the mediation test that was applied using the process macro method have proven customer integration to have an intermediary role in internal integration’s impact on speed and reliability in logistics.